Identifying the contextual barriers and opportunities pertaining to the sustainable refurbishment of existing public sector office buildings in the inner city area of Johannesburg, South Africa - Govender, Sathia (My University, 2019)
In most cases refurbishment is driven by cosmetic upgrade requirements. The existing building stock possesses significant opportunity to improve building performance and reduce its negative impacts on the environment. The local green building environment in the public sector is analysed. The focus is existing office buildings. The relevant policies and frameworks related to sustainable development is collated and policy objectives are identified and discussed. The research approach adopted is that of a case study method. A comparative case study approach is selected for this study. Key themes emerged from the literature review and these themes informed the semi-structured interviews that took place with the appropriate stakeholders involved in the cases. Three different types of case studies were identified and documented. Comparative case studies emphasise comparison within and across contexts. They involve the analysis and synthesis of the similarities, differences and patterns across two or more cases that share a common goal. The cases were compared, success factors are assessed and findings presented. A conclusion is presented based on these key themes. Refurbishment of existing buildings is considered the most sustainable response when considered against other activities in the built environment. A single case type of the three selected, the PPP model, emerges as the preferred type offering the greatest potential supporting the sustainable refurbishment of existing public sector office buildings
A research report submitted to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science (Building). Johannesburg, August 2019
Keywords: Office buildings--Design and construction; Sustainable buildings--South Africa